THE EFFECT OF HEAT TREATMENT AND PRESSING AT 400 °C WITH COCONUT SHELL CHARCOAL MEDIA ON THE HARDNESS, MICROSTRUCTURE, AND DENSITY OF AL-SI ALLOYS - Masyrukan Masyrukan; Agung Setyo Darmawan; Agus Hariyanto; Pramuko Ilmu Purboputro; Hanif Alfian Ihwanudin; Muhammad Ibnu Pamungkas (Media Mesin: Majalah Teknik Mesin, 2022)
This study aims to determine the effect of the heat treatment process and pressing on hardness, density, and morphological changes in the microstructure of Al-Si alloys. In this study, the medium used was coconut shell charcoal with a mesh size of 80 at a heat treatment process of 400 °C and a holding time of 75 minutes. The pressing was carried out with a load of 150 N. The result of this research is an increase in the hardness of the Al-Si alloy with an average value of 133 VHN after the Heat Treatment and pressing process. In the microstructure, there is a morphological change in the Al-Si alloy with the reduction of Si elements and also an increase in the density value after the heat treatment process.